Five-Level Single Source Voltage Converter Controlled Using Selective Harmonic Elimination - Ibrahim Haruna Shanono; Nor Rul Hasma Abdullah; Aisha Muhammad (Institute of Advanced Engineering and Science, 2018)
The paper presents a 5-level cascaded H-bridge voltage source inverter. The converter topology composed of two-cascaded H-bridge modules connected in parallel and powered by a single DC source. The benefit of this topology in comparison with the conventional H-Bridge configuration is that it uses single input DC source instead of two to achieve the same output steps/levels. Selective Harmonic Elimination (SHE) is the modulation technique employed. The generated non-linear transcendental equations are solved using an optimised Genetic algorithms to find the switching angles. This property makes the topology and the control function suitable for three phase applications where triplen harmonics are said to cancel out at the line-to-line voltages. This concept of SHE modulation extends the value of the filter cut-off frequency, which translates to smaller sized filter, compact cooling system and reduced system weight. This advantage makes the topology attractive to automotive and renewable energy applications. The topology was simulated using PSIM software.